Knowledge, comprehension, attitude to and practice of the five levels of prevention in child healthcare in a Nigerian teaching hospital - West, Timipah P.; Tabansi, Petronilla N.; Yarhere, Iroro; Nkanginieme, Kanu E. O. (International Journal of Research in Medical Sciences, 2023)
Background: Preventive Paediatrics involves all activities geared towards protecting, promoting and maintaining the health and wellbeing of children. The aim of this study to determine the knowledge, attitude and practice of the five levels of prevention by child-care doctors at the University of Port Harcourt Teaching Hospital. Methods: This was a descriptive cross-sectional survey using a self-administered questionnaire. Information on socio-demographics, knowledge, comprehension and attitude of the respondents towards the five levels of prevention and its utilization by the doctors at the University of Port Harcourt Teaching Hospital was sought. Data were analyzed using descriptive statistics. Results: 295 doctors participated. 26 (8.8%) doctors had good knowledge of the five levels of prevention. As the doctors’ age increased, they were less likely to be knowledgeable about the levels of prevention (OR=0.955; 95% CI: 0.917-0.995; p-value=0.029). Doctors in Pediatrics were four times more likely to be knowledgeable about the levels of prevention than the others (OR=3.637; 95% CI: 1.496-8.844; p-value= 0.004). 287 (97.3%) doctors had good attitude towards preventive activities while practice was by 222 (75.3%). There were no significant differences across gender, age, department, designation and years of practice. Doctors with good knowledge significantly practiced more levels of prevention compared to those with poor knowledge (p=0.049, 0.024, 0.001 and 0.010 respectively). Conclusions: Majority of the doctors have poor knowledge of the five levels of prevention, despite having a good attitude and practice which suggests a knowledge-practice gap. Interventions to improve doctors’ knowledge are recommended.